2017
DOI: 10.1016/j.jsxm.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Blood Pressure and Erectile Dysfunction in Men Without Previously Diagnosed Hypertension

Abstract: Background Erectile dysfunction (ED) is the most common male sexual disorder that affects all age groups and has a close association with essential hypertension. Aim To characterize the relation of blood pressure and ED in detail. Methods A cross-sectional population-based study of 45- to 70-year-old men without previously diagnosed hypertension, cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…Several trials have confirmed the strong association between ED and hypertension 3,62‐66 . Results from the SPRINT trial showed that ED was very common in middle‐aged and older men with hypertension, affecting 59.9% of the patients.…”
Section: The ‘Complicated Role’ Of Complications and Cofactors In The...mentioning
confidence: 94%
See 1 more Smart Citation
“…Several trials have confirmed the strong association between ED and hypertension 3,62‐66 . Results from the SPRINT trial showed that ED was very common in middle‐aged and older men with hypertension, affecting 59.9% of the patients.…”
Section: The ‘Complicated Role’ Of Complications and Cofactors In The...mentioning
confidence: 94%
“…Several trials have confirmed the strong association between ED and hypertension. 3 , 62 , 63 , 64 , 65 , 66 Results from the SPRINT trial showed that ED was very common in middle‐aged and older men with hypertension, affecting 59.9% of the patients. The authors, however, concluded that this percentage may be higher considering that patients who already received phosphodiesterase (PDE) inhibitor treatment were also included in the study.…”
Section: The ‘Complicated Role’ Of Complications and Cofactors In The...mentioning
confidence: 99%
“…Erectile dysfunction (ED) or impotence is characterised by persistent inability to develop and maintain an erection of the penis in men for intercourse [1]. ED is one of the most common sexual disorders in males, and it affects about half of the male population between 40 and 70 years old [2,3]. ED is a neurovascular phenomenon modulated by hormonal, local biochemical, and biomechanical factors [4-7].…”
Section: Introductionmentioning
confidence: 99%
“…ED is a neurovascular phenomenon modulated by hormonal, local biochemical, and biomechanical factors [4-7]. Erectile dysfunction may signal serious underlying diseases, such as hypertension [2], diabetes mellitus [8,9], cardiovascular disease [10,11], peripheral vascular disease [12], and other endocrine [13] and neurological disorders [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that ED was associated with ventricular hypertrophy confirmed the study of Kakkavas et al [22] in which it was reported that ED was associated with left ventricular diastolic dysfunction, which is an early abnormality in the evolution of hypertensive LVH. Heikkilä et al [23] found a U-shaped correlation between ED and diastolic BP, which confirms the link between ED and severity of hypertension. ED and hypertension share a common pathogenesis, namely vas- Data are presented as % (n).…”
Section: Discussionmentioning
confidence: 73%